(untitled) (Research, Society and Development, 2024)
The effects of thalassemia major and minor on bone density and skeletal development can have negative impacts on affected individuals when compared to the general population. It is therefore of interest to investigate the impact of these hematological disorders on bone density and skeletal development, and how these effects compare with each other and with healthy individuals. The aim of this article is therefore to present a systematic review of the effects of thalassemia major and minor on bone density and skeletal development. Initially, 11 articles were found in the Pubmed, Cochrane and BvSalud databases. Of these, we included articles that assessed patients with thalassemia major and minor, used methods to assess bone density and skeletal development, and compared the results with healthy individuals; and excluded studies that did not distinguish between thalassemia major and minor, did not use validated assessment techniques or did not present comparative data; a total of 5 articles were used. The studies reviewed point to a substantial impairment of bone formation and maintenance in individuals and animal models with thalassemia, showing that alterations in osteoblastic function and an increase in osteoclastic activity contribute to an imbalance in the bone remodeling process, although further studies are needed to clarify this.